Pengaruh Unggahan Instagram Go Green Terhadap Intensi Membeli Produk Organik Bagi Mahasiswa di Kota Batam - Muhammad Ardiansyah; Wilsen Chanrico (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
In Indonesia, problems regarding the natural environment are very widespread these days, various kinds of natural events are affected by environmental problems such as damage to coral reefs, lots of plastic waste, increasing levels of pollution in the air and deforestation. Influencing the interest of an individual is not easy and tends to be complicated so it requires knowledge that must be disseminated to consumers - consumers. This research aims to try to attract students in Batam City to increase the intensity of buying organic products by spreading an Instagram post that has been designed using editing application such as CorelDRAW. After that the data that has been collected will be analyzed using linear regression analysis techniques using the SPSS IBM Statistics version 26 application. From the questionnaires that have been collected there are 411 respondents collected. The results of this study show that the Instagram posts that have been designed can attract the attention of students in Batam City to intensively buy organic products, but still need further research in order to get more detailed and satisfying results.